Percutaneous Image-guided Surgery Training: Model IHU-DAICIM. Issue 1 (February 2018) - Gimenez, Mariano Eduardo; Davrieux, Carlos Federico; Serra, Edgardo; Palermo, Mariano; Houghton, Eduardo Javier; Acquafresca, Pablo Agustin; Dallemagne, Bernard; Kwak, Jung-Myun; Gonzalez, Cristians Alejandro; Marescaux, Jacques
Abstract : The evolution of guided imaging surgery is well known in recent years. As the field of action becomes more specific, learning and teaching are also more specific. State-of-the-art medical training should be mandatory in the field of general medicine and surgery in particular. In this work, we report on how to create a model for the formation of guided surgery by images in a simple and fast way, and its implementation by young surgeons. Pig models have been used in which collections made by bovine small intestine and simulated tumor lesions have been placed. Several types of image-guided procedures have been performed. No major complications were found during the development of the model or during its use. It is possible to develop a quick, simple, and safe living training model that can be used immediately after preparation.